Proses pembangunan ekonomi dalam perspektif historis komparasi antara Indonesia dan Jepang - Hary Setyo Adji (Economic Journal of Emerging Markets, 1997)
Disconnection of modern and traditional sector is often assumed as the effect of government policies that are very oriented on economic growth. Whereas, economic development is a long term process. In this context, a discourse will be incomprehensive if it doesn't look at the roots of the government policies in the early days of Indonesian development process.